Gold Tested in Fire : A New Pentecost for the Catholic Priesthood - Witherup, Ronald D., 1950- (Book collections on Project MUSE., 2012)
The recent Year for Priests focused considerable attention on the priesthood, resulting in many books, articles, retreats, conferences, and symposia. In Gold Tested in Fire, Ronald D. Witherup, SS, makes an important new contribution. Intersecting scriptural and theological context with lived pastoral insight, Witherup explores both classic and contemporary understandings of the priesthood, offers insights into the four pillars suggested for priestly formation, and looks at the charism of priests, and the need for ongoing formation across a life-span. Having engaged in priestly formation in seminaries for a number of years, Witherup moves beyond overly idealized or pietistic approaches to the presbyteral life to offer key insights on the challenges and rewards inherent in contemporary priestly ministry. Underlying his approach is the firm conviction that the present testing in the priesthood is a profound summons to a new Pentecost, an opportunity for the priesthood to be cleansed and remade, and ultimately stronger.